Association of hospital performance measures with readmissions for patients with heart failure: A report from JROAD-DPC study. (1st October 2021) - Nakao, Kazuhiro; Yasuda, Satoshi; Noguchi, Teruo; Sumita, Yoko; Nakao, Yoko M.; Nishimura, Kunihiro; Nakai, Michikazu; Miyamoto, Yoshihiro; Tsutsui, Hiroyuki; Saito, Yoshihiko; Komuro, Issei; Gale, Chris P.; et al.
Abstract: Background: Measuring quality of care is central to quality improvement. Improving outcomes for heart failure (HF) may relate to hospital care delivery. However, there is limited nationwide data on the relationship between hospital-level HF performance measures and clinical outcomes. Methods: From the Japanese Registry of All cardiac and vascular Diseases (JROAD-DPC) database, 83, 567 HF patients hospitalised in 731 certificated hospitals in 2014 by the Japanese Circulation Society were analysed. Five performance measures were prescription rate of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker, beta-blocker, and mineralocorticoid receptor antagonist and measurement rate of echocardiography and B-type natriuretic peptide during hospitalisation. Relationships between these measures and 1-year readmission due to HF were analysed. Composite performance score (CPS) obtained from the five performance measures and outcomes were also analysed. We also investigated the relationships between CPS and hospital structural factors. Results: From the cohort (mean age; 78.2 years, woman 48.4%), HF readmission rate at 1 year was 19.6% ( n  = 16, 368). Readmission rate decreased with higher quartiles of prescription rate in each medication and diagnostic performance rates. The highest CPS group was associated with a 15% risk reduction in HF readmission compared with the lowest CPS group (hazard ratio, 0.85, 95% confidence interval [0.80–0.89], p  < 0.001) after covariate adjustment. Several structural factors such as number of cardiology specialists, hospital case volume for HF, and presence of cardiac surgery division were associated with high CPS. Conclusion: Higher hospital performance measures for HF were inversely associated with HF readmissions. Graphical abstract: Unlabelled Image Highlights: Hospital-based performance measures for HF including prescription (ACEI/ARB, BB, and MRA) and examination (Echo and BNP) were associated with HF. Composite performance of hospitals was associated positively with several hospital structural factors. Nation-wide evaluation and improvement of hospital-level performance may be significant to reduce HF readmissions in ageing societies like Japan.